2018 Energy Balances - United Nations Department of Economic; Social Affairs (United Nations, 2021)
This publication contains energy balances for about 220 countries and territories, showing production, trade, transformation and consumption (by sector) in energy units for all energy products. It presents energy data for countries and areas in a format which shows the overall picture of the production, trade, transformation and consumption of energy products utilized in the region. Such a format is useful in assessing and analyzing supply and consumption patterns across both products and countries in detail on an internationally comparable basis.